2015
DOI: 10.1093/femsle/fnv006
|View full text |Cite
|
Sign up to set email alerts
|

msaABCR operon positively regulates biofilm development by repressing proteases and autolysis in Staphylococcus aureus

Abstract: Staphylococcus aureus is an important human pathogen that causes nosocomial and community-acquired infections. One of the most important aspects of staphylococcal infections is biofilm development within the host, which renders the bacterium resistant to the host’s immune response and antimicrobial agents. Biofilm development is very complex and involves several regulators that ensure cell survival on surfaces within the extracellular polymeric matrix. Previously, we identified the msaABCR operon as an additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 51 publications
3
37
0
Order By: Relevance
“…Previously, we have shown that the msaABCR operon is involved in virulence, biofilm development and antibiotic resistance (Sambanthamoorthy et al, 2006(Sambanthamoorthy et al, , 2008Sahukhal & Elasri, 2014;Samanta & Elasri, 2014;Sahukhal et al, 2015). In this study, we found that MsaB, encoded by the msaABCR operon, binds directly to a previously identified 10 bp inverted regulatory repeat located immediately upstream from the identified cap promoter region.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Previously, we have shown that the msaABCR operon is involved in virulence, biofilm development and antibiotic resistance (Sambanthamoorthy et al, 2006(Sambanthamoorthy et al, , 2008Sahukhal & Elasri, 2014;Samanta & Elasri, 2014;Sahukhal et al, 2015). In this study, we found that MsaB, encoded by the msaABCR operon, binds directly to a previously identified 10 bp inverted regulatory repeat located immediately upstream from the identified cap promoter region.…”
Section: Discussionsupporting
confidence: 49%
“…However, given the pleiotropic effect of deletion of the msaABCR operon, we cannot rule out factors other than the lack of capsule production in the reduced survival of the msaABCR mutant. Indeed, we have also shown in several of our studies that the msaABCR operon plays a role in regulation of many virulence factors, biofilm development and antibiotic resistance (Sambanthamoorthy et al, 2006(Sambanthamoorthy et al, , 2008Samanta & Elasri, 2014;Sahukhal & Elasri, 2014;Sahukhal et al, 2015). Further studies are needed to examine the putative contribution of other factors affected by the msaABCR operon.…”
Section: Deletion Of Msaabcr Operon Leads To Reduced Survival In Bloodmentioning
confidence: 69%
See 1 more Smart Citation
“…We have also shown that msaABCR mutants are defective in persister cell formation under cell wall-targeting antibiotic (vancomycin and daptomycin) stress conditions in the USA300 LAC strain background (26). Increases in Triton X-100-induced autolysis and protease production are also major phenotypes of the msaABCR-deletion mutant (21,22). We previously showed that the msaABCR operon represses protease activity regulating the expression of four extracellular proteases (Aur, Scp, Ssp, and Spl) in various growth phases, including the early exponential growth phase (21,23).…”
mentioning
confidence: 69%
“…These reports have rekindled interest in targeting genes involved in the maintenance of cell wall integrity and ultimately resensitizing resistant strains (4,7,(13)(14)(15)(16)(17)(18)(19)(20). Previously, we showed that the msaABCR operon plays a role in biofilm development, virulence, persister cell formation, and antibiotic resistance in S. aureus (21)(22)(23)(24)(25)(26). The msaABCR operon is a four-gene operon composed of msaA, msaB, msaC, and an antisense RNA, msaR (23).…”
mentioning
confidence: 99%